An Assessment of the economic and social impacts of climate change on the agriculture sector in the Caribbean (UN New YorkUS, 2013)
Determines the value of impacts due to climate change on the agricultural sector in the Caribbean under the Intergovernmental Panel on Climate Change (IPCC) Special Report on Emissions Scenarios A2 and B2. Aims to evaluate the direction and magnitude of the potential impacts of climate change on aggregate agricultural output and other key agricultural indicators. Analyses the benefits and costs of the key adaptation strategies identified by Caribbean governments.
Bibliography: p.67-72